Associations between the Dietary Inflammatory Index and depression among pregnant and postpartum women: analysis of NHANES 2005–2018 - Qiao, Jian; Han, Aiqing; Qu, Yannv; Zhang, Li (Frontiers in Nutrition, 2025)
BackgroundPerinatal depression, which occurs during pregnancy or after childbirth, is a common and serious complication of pregnancy. Chronic low-grade inflammation has been implicated in the pathophysiology of depression. The Dietary Inflammatory Index (DII) is a validated measure of the inflammatory potential of a diet, where higher scores indicate a more proinflammatory diet. This study examined the association between DII and depression among pregnant and postpartum women, with a focus on potential non-linear (threshold) effects.MethodsWe analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2005–2018. The sample included 1,093 women who were either pregnant or in the postpartum period within 18 months. Dietary intake was assessed via 24-h recall, and DII scores were calculated for each participant. Depressive symptoms were measured using the Patient Health Questionnaire-9 (PHQ-9); we defined depression as a PHQ-9 score ≥10, indicating moderate or greater depressive symptoms. Weighted multivariate logistic regression was used to estimate odds ratios (ORs) for depression in relation to DII scores, and weighted linear regression was used to assess the association between DII scores and PHQ-9 total scores. Models were adjusted for potential confounders, including age, race, poverty income ratio, marital status, smoking status, education level, BMI and WBC. We tested for non-linear relationships using a generalized additive model (GAM). A two-piecewise linear regression model was then applied, and a log-likelihood ratio test was used to compare the piecewise model to a single-linear-term model. Sensitivity analyses were conducted to check the robustness of the findings.ResultsThe mean age of pregnant and postpartum women was 28.88 (95% CI 28.34–29.42) years. Overall, 7.1% participants met the criteria for moderate/severe depression (PHQ-9 score ≥10). DII scores ranged from anti-inflammatory to proinflammatory; approximately 21.9% of the sample had a highly proinflammatory diet (DII > 2.87). We observed a non-linear association between DII and depression (P for non-linearity = 0.008 for the threshold effect). In adjusted weighted logistic models, among women with DII > 2.87, each 1-unit increase in DII was associated with an OR = 2.81 for depression (95% confidence interval 1.07–7.38, p = 0.039). Consistently, in the weighted linear regression, when the DII exceeded 2.87, each additional DII point corresponded to an increase of β = 1.59 points in the PHQ-9 score (95% CI 0.02–3.17, p = 0.047), indicating worse depressive symptom severity with more proinflammatory diets. The associations remained significant and of similar magnitude in the sensitivity analyses.ConclusionIn this cross-sectional study of pregnant and postpartum women in the U. S., a higher Dietary Inflammatory Index was associated with a greater risk of depression, but this relationship was markedly non-linear. Diets with very high proinflammatory potential were linked to significantly increased odds of perinatal depression, whereas more anti-inflammatory diets did not result in a further decrease in depression risk below that threshold. However, owing to the inherent limitations of the study design, causality cannot be established, and a reverse effect of depressive symptoms on dietary choice cannot be ruled out.